2019
DOI: 10.1155/2019/5013592
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Microenvironment and Cell Fusion

Abstract: Cell fusion is a highly regulated biological process that occurs under both physiological and pathological conditions. The cellular and extracellular environment is critical for the induction of the cell–cell fusion. Aberrant cell fusion is initiated during tumor progression. Tumor microenvironment is a complex dynamic system formed by the interaction between tumor cells and their surrounding cells. Cell–cell fusion mediates direct interaction between tumor cells and their surrounding cells and is associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 122 publications
(137 reference statements)
1
32
0
2
Order By: Relevance
“…Cancer cell fusion has emerged as a fundamental non-genetic mechanism that contributes to intratumor heterogeneity, resulting in tumor progression (invasive growth and metastasis) and therapy resistance. As recently pointed out by different authors [136][137][138][139], the potential role of fusion between cancer cells and motile leukocytes in promoting metastasis was proposed by the German pathologist Prof. Otto Aichel nearly a century ago. This intriguing hypothesis remained controversial during the 20th century when the somatic mutation theory of carcinogenesis was the dominant force driving cancer research.…”
Section: The Role Of Cancer Cell Fusion In Metastasis and Therapy Resmentioning
confidence: 94%
See 1 more Smart Citation
“…Cancer cell fusion has emerged as a fundamental non-genetic mechanism that contributes to intratumor heterogeneity, resulting in tumor progression (invasive growth and metastasis) and therapy resistance. As recently pointed out by different authors [136][137][138][139], the potential role of fusion between cancer cells and motile leukocytes in promoting metastasis was proposed by the German pathologist Prof. Otto Aichel nearly a century ago. This intriguing hypothesis remained controversial during the 20th century when the somatic mutation theory of carcinogenesis was the dominant force driving cancer research.…”
Section: The Role Of Cancer Cell Fusion In Metastasis and Therapy Resmentioning
confidence: 94%
“…This intriguing hypothesis remained controversial during the 20th century when the somatic mutation theory of carcinogenesis was the dominant force driving cancer research. In the past decade, however, a significant number of reports have underscored the importance of cell fusion in tumor progression and therapy resistance in a wide range of malignancies (e.g., [136][137][138][139][140][141][142][143][144][145]). In a recent study reported by Gast and associates [144], for example, cancer cell-leukocyte hybrids were detected in peripheral blood of cancer patients, and the numbers of such hybrids in the patient's blood correlated with disease stage and predicted overall survival.…”
Section: The Role Of Cancer Cell Fusion In Metastasis and Therapy Resmentioning
confidence: 99%
“…Actually, a lot of studies have reported that cancer cells can spontaneously fuse among themselves [38] or with other different types of normal cells such as epithelial cells [39–42], endothelial cells [43–45], and stromal cells [46,47] to generate phenotypic heterogeneity. Additionally, many kinds of cancer cells can fuse with macrophages that are considered as an important fusogenic candidate in the tumor microenvironment [48]. Early studies discovered that the hybrids derived from fusion between macrophages and a kind of nonmetastatic melanoma cells exhibited polyploid, which could spontaneously fuse with host cells in mice to form lung metastasis [49].…”
Section: Cell Fusionmentioning
confidence: 99%
“…An irregularly shaped solid tumor, actually is not composed of pure cell population but a cellular mixture from single or multiple clones of stem cells [1], which are also characterized with different biological properties including different resistance to chemotherapeutic drugs. Plus the complex tumor microenvironment due to different degree of hypoxia, glucose level, and blood supply [2], the fact that a solid tumor is composed of a mixture of tumor cells with different resistant degree is easily understandable. Thus, how do these different cell populations affect each other in a solid tumor microenviroment?…”
Section: Hegselmann-krause (Hk) Model and Prediction For Drug Resistancementioning
confidence: 99%